Application of Liquid Chromatography-Tandem Mass Spectrometry for the Detection of Paralytic Shellfish Poison in Bivalve Shellfish and Its Influencing Factors - DENG Yuxiang, WU Haiyan, XU Xizhen, ZHAO Huihui, TAN Zhijun, ZHENG Guanchao (Shipin Kexue)
Paralytic shellfish poison (PSP) is one of the most hazardous and widely distributed marine biotoxins, posing a significant threat to human health, fishery economy, and marine environment. Bivalve shellfish is the primary source of PSP for consumers. With the frequent occurrence of PSP poisoning incidents, there is a growing global demand for PSP detection technology in bivalve shellfish. This article begins by introducing the physicochemical properties of PSP. It then summarizes the advantages and disadvantages of liquid chromatography-tandem mass spectrometry (LC-MS/MS) in the detection of PSP in bivalve shellfish from four aspects: pretreatment extraction and purification, instrumental conditions, matrix effects, and method validation. Comparative analysis reveals that 1% acetic acid is the most commonly used extraction solvent in LC-MS/MS analysis of PSP. Graphitized carbon black (GCB) packing and hydrophilic interaction liquid chromatography (HILIC) are more suitable for the purification and separation of PSP extracts from bivalve shellfish, respectively. The major factors affecting matrix effects includes endogenous interferences such as phospholipids and proteins and exogenous interferences such as organic substances and polymer residues in the detection methods. This article focuses on the research and development trend of LC-MS/MS to provide references for the detection of PSP in bivalve shellfish and to offer technical support for the green development of the shellfish aquaculture industry and government regulation.